2001
DOI: 10.1161/hs1101.097391
|View full text |Cite
|
Sign up to set email alerts
|

Major Variation in Carotid Bifurcation Anatomy: A Possible Risk Factor for Plaque Development?

Abstract: Background and Purpose-Why is carotid plaque often so strikingly asymmetrical within individuals, and why does the extent of disease vary so considerably between individuals with similar systemic risk factors? Variability of carotid bifurcation anatomy is a possible explanation. Flow models suggest that vessel anatomy, in particular vessel diameter and area ratios, affects plaque formation at arterial bifurcations. However, carotid bifurcation anatomy could only be a major risk factor for plaque formation if i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
87
1
11

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 34 publications
(35 reference statements)
2
87
1
11
Order By: Relevance
“…Instead, Schulz and Rothwell demonstrated wide variations in the relative dimensions of carotid bifurcation of older adults with Ͻ30% stenosis 4 ; however, our group subsequently found significantly narrower variations in the geometries of ostensibly healthy young adults. 5 The geometric risk hypothesis also hinges on the assumption of a direct relationship between exposure to disturbed flow and purported geometric risk factors.…”
contrasting
confidence: 60%
“…Instead, Schulz and Rothwell demonstrated wide variations in the relative dimensions of carotid bifurcation of older adults with Ͻ30% stenosis 4 ; however, our group subsequently found significantly narrower variations in the geometries of ostensibly healthy young adults. 5 The geometric risk hypothesis also hinges on the assumption of a direct relationship between exposure to disturbed flow and purported geometric risk factors.…”
contrasting
confidence: 60%
“…Vessel anatomy in turn influences the hemodynamic forces and as such the left carotid artery may be exposed to higher arterial pressures. 6,32 Flow models have shown that atherosclerotic plaques preferentially develop in areas with low wall shear stress, such as at bifurcations or inner curves. 33 Wall shear stress and stress inside the vessel wall may affect plaque formation and composition by causing alterations in wall structure and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic plaques usually reside in artery bifurcations with complex flow patterns (6,7,10,13,15,17). Because of its clinical relevance to stroke (9), the morphometry of human carotid artery bifurcation [comprised of the left and right common (CCA), internal (ICA), and external (ECA) carotid arteries] (16) has received intensive investigation (3,23,24,27). Researchers have proposed various geometric risk factors for the incidence of atherosclerotic plaques, e.g., increased bifurcation angle and enhanced differences in area ratios including the flare, proximal curvature, and tortuosity of ICA.…”
mentioning
confidence: 99%